## 2 (3x + 1) = 7x – 5

### x = 7

To solve this equation, follow these steps:

Step 1: Distribute the 2 to the terms inside the parenthesis.

2(3x + 1) = 7x – 5

6x + 2 = 7x – 5

Step 2: Move all the x terms to one side and all the constant terms to the other side by subtracting 6x from both sides and adding 5 to both sides.

6x + 2 – 6x + 5 = 7x – 5 – 6x + 5

7 = x

Step 3: Check the solution by substituting the value of x back into the original equation.

2(3(7) + 1) = 7(7) – 5

44 = 44

Therefore, x = 7 is the solution to the equation 2(3x + 1) = 7x – 5.

##### More Answers:

Master The Art Of Communication: Boost Your Vocabulary With OppositesNegative Numbers: A Crucial Tool For Solving Complex Mathematical Problems

How To Solve For X: Step-By-Step Guide For The Equation 2(X+1)=6X-46

Error 403 The request cannot be completed because you have exceeded your quota. : quotaExceeded